A Game of Closeness or Alienation - Poliszczuk, Jarosław (Poznańskie Studia Slawistyczne, 2021)
Mykhailo Nayenko’s book of memoirs Озон зарубіжжя (Ozone of Abroad) is about author’s journeys to different countries and cultures. Mykhailo Nayenko is a well-known professor, who runs literary researches from the early 1980th for today. The book presented in the review, shows how academic landscape of Ukraine and Eastern Europe was changing after the collapse of Soviet Union. We can also notice some changes in author’s consciousness too as he tried to find his own place in the world without strict borders, in the conditions of free thoughts and possibility of speaking without censorship.